Experimental Analysis of Fresnel Lens-Based Solar Desalination Systems with Copper Receivers for Enhanced Thermal and Electrical Performance - Mahmood, Abdulkareem Nasir; Azmi, Syahrul Ashikin binti; El-Khazali, Reyad; Çiçek, Adem; Assi, Saad A.; Al-Naimi, Taha Mahmoud; Majdi, Hasan S.; Bektas, Enes; Radhi, Ahmed Dheyaa; Hussain, Abadal-Salam T. (Association for Scientific Computing Electronics and Engineering (ASCEE), 2025)
Solar desalination represents a breakthrough technology for creating sustainable freshwater because it meets both the water quality standards and technology efficiency requirements of modern times. The current desalination methods, which depend on fossil fuels, encounter major obstacles regarding their energy requirements and economical performance. The research investigates the improvement of solar desalination performance through coupling Fresnel lens technology with copper-based receivers to maximize thermal characteristics and power generation benefits. This research successfully unites Fresnel lenses of high performance with copper receivers to reach increased steam temperatures alongside power production during the same procedure. The research team performed experimental tests using a system that included four large Fresnel lenses in Sharjah, UAE. Under different operating settings, the system demonstrated its performance by measuring its flow rates together with ambient temperatures and recording the steam output values. The experimental data showed that bigger Fresnel lenses boosted the steam temperature beyond 1000°C as well as pushing pressure levels to 8 bar, which led to remarkable system efficiency benefits. The copper receiver system generated 775 mA DC electric current, which collectively enhanced the system's power efficiency. The tested combination of Fresnel lenses and copper receivers demonstrates an effective way to enhance solar desalination systems, according to observed experimental data. The dualfunction technology combines desalination efficiency improvement with electricity production capabilities to establish a sustainable freshwater production method for arid regions. This investigation creates a basis for developing economical renewable desalination systems going forward.